2023
DOI: 10.1161/circulationaha.123.064121
|View full text |Cite|
|
Sign up to set email alerts
|

Jmjd4 Facilitates Pkm2 Degradation in Cardiomyocytes and Is Protective Against Dilated Cardiomyopathy

Abstract: BACKGROUND: A large portion of idiopathic and familial dilated cardiomyopathy (DCM) cases have no obvious causal genetic variant. Although altered response to metabolic stress has been implicated, the molecular mechanisms underlying the pathogenesis of DCM remain elusive. The JMJD family proteins, initially identified as histone deacetylases, have been shown to be involved in many cardiovascular diseases. Despite their increasingly diverse functions, whether JMJD family members play a role in DCM r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 60 publications
1
13
0
Order By: Relevance
“…1 Jmjd4, however, belongs to those smaller Jmjd proteins well below 100 kDa, which have few known domains besides the Jmjc domain and normally lack histone demethylase activity. 1 In fact, Pkm2, identified in our work, 2 is among a handful Jmjd4 substrates characterized so far, the list of which may certainly grow with future studies.…”
Section: In Responsementioning
confidence: 72%
See 2 more Smart Citations
“…1 Jmjd4, however, belongs to those smaller Jmjd proteins well below 100 kDa, which have few known domains besides the Jmjc domain and normally lack histone demethylase activity. 1 In fact, Pkm2, identified in our work, 2 is among a handful Jmjd4 substrates characterized so far, the list of which may certainly grow with future studies.…”
Section: In Responsementioning
confidence: 72%
“…2 It is not uncommon that phenotypes of loss-of-function are not the opposite of gain-of-function, or enzymatic activation, in a biological system, because deviation toward either direction from the optimal quantity, or activity, of a tightly regulated key protein may deteriorate cellular and tissue homeostasis. In addition, although we did not genetically manipulate Pkm2 in our study, 2 the mutual compensation between Pkm1 and Pkm2 , which differ by only 1 alternatively spliced exon, is a well-documented phenomenon. An earlier study 4 evidently showed that when the Pkm1 - or Pkm2 -specific exon is deleted in cardiomyocyte, the expression of the other elevates to compensate.…”
Section: In Responsementioning
confidence: 99%
See 1 more Smart Citation
“…We read with interest the article by Tang et al 1 reporting that pressure overload reduces myocardial Jmjd4 expression and leads to the accumulation of inactive Pkm2 dimer, which results in progressive dilated cardiomyopathy and heart failure. Jmjd4 hydroxylates Pkm2 to promote its degradation through chaperone-mediated autophagy.…”
Section: To the Editormentioning
confidence: 99%
“…Pyruvate kinase M2 (PKM2) is a specific isoform of the pyruvate kinase enzyme, crucial for cellular metabolism, particularly in glycolysis. Its involvement spans various physiological and pathological processes, including cell proliferation, metabolic regulation, and tumorigenesis [8][9][10]. The pivotal role of PKM2 in regulating cellular energy metabolism and growth is of profound interest in disease research and therapy.…”
Section: Introductionmentioning
confidence: 99%